Molecular imaging on ACE2‐dependent transocular infection of coronavirus. Issue 10 (5th July 2022) - Li, Danni; Xiong, Liyan; Pan, Guixia; Wang, Tingfang; Li, Rou; Zhu, Lizhi; Tong, Qianqian; Yang, Qinqin; Peng, Ye; Zuo, Changjing; Wang, Cong; Li, Xiao
Abstract: A transocular infection has been proved as one of the main approaches that severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) invades the body, and angiotensin‐converting enzyme 2 (ACE2) plays a key role in this procedure. Dynamic and quantitative details on virus distribution are lacking for virus prevention and drug design. In this study, a radiotraceable pseudovirus packed with an enhanced green fluorescent protein (EGFP) gene, 125 I‐CoV, was prepared and inoculated in the unilateral eye of humanized ACE2 (hACE2) mice or ACE2‐knockout (ACE2‐KO) mice. Single‐photon emission computed tomography/computed tomography images were acquired at multiple time points to exhibit ACE2‐dependent procedures from invasion to clearance. Positron emission tomography (PET) and western blot were performed to quantify ACE2 expression and verify the factors affecting transocular infection. For the transocular infection of coronavirus (CoV), the renin–angiotensin–aldosterone system (RAAS), lungs, intestines, and genital glands were the main targeted organs. Due to the specific anchor to ACE2‐expressed host cells, virus concentrations in genital glands, liver, and lungs ranked the top three most and stabilized at 3.75 ± 0.55, 3.30 ± 0.25, and 2.10 ± 0.55% inoculated dose (ID)/mL at 48 h post treatment. Meanwhile, ACE2‐KO mice had already completed the in vivo clearance. In consideration of organ volumes, lungs (14.50 ± 3.75%ID) and liver (10.94 ± 0.71%ID) were the main in‐store reservoirs of CoV. However, the inoculated eye (5.52 ± 1.85%ID for hACE2, 5.24 ± 1.45%ID for ACE2‐KO, p > 0.05) and the adjacent brain exhibited ACE2‐independent virus infection at the end of 72 h observation, and absolute amount of virus played a key role in host cell infection. These observations on CoV infection were further manifested by infection‐driven intracellular EGFP expression. ACE2 PET revealed an infection‐related systematic upregulation of ACE2 expression in the organs involved in RAAS (e.g., brain, lung, heart, liver, and kidney) and the organ that was of own local renin–angiotensin system (e.g., eye). Transocular infection of CoV is ACE2‐dependent and constitutes the cause of disturbed ACE2 expression in the host. The brain, genital glands, and intestines were of the highest unit uptake, potentially accounting for the sequelae. Lungs and liver were of the highest absolute amount, closely related to the respiratory diffusion and in vivo duplication. ACE2 expression was upregulated in the short term after infection with CoV. These visual and quantitative results are helpful to fully understanding the transocular path of SARS‐CoV‐2 and other CoVs.